故障树分析法在球磨机传动齿轮中的应用 - 闫存富; 刘朝华 (Jixie chuandong)
The failure mode of drive gear is analyzed by fault tree analysis.First,the failure tree is established,secondly,the minimal cut sets are caculated,then the qualitative and quantitative analysis are carried out.The result proveds that this method is convenient,simple and practical.